A REVIEW STUDY ON THE CONCEPT OF ATULYAGOTRIYA MARRIAGES AND ITS SCIENTIFIC VALIDITY - Kumar, Shobhit (International Journal of Ayurveda and Pharma Research, 2016)
Ayurveda is a thousand of years old science and it is very interesting fact that it is covering every aspect of human beings life i.e. physical, psychological, social and related to soul. Ayurvedic Acharya mentioned Atulyagotriya marriage concept right from Samhita Kala and explained bad effect of Tulyagotriya marriages. Many Samhitas like Charka, Kashyapa and Bhela Samhita mentioned separate chapters regarding this subject. Though studies are done regarding bad effect of consanguineous marriages in ancient and current sciences as well, but in seriousness are not disseminated to the nuke and corner of the society through scientific reports. Consanguineous marriages incidences are also may be varying from area to area or from culture to culture. People who are blood relatives share a greater proportion of the same genes than unrelated people do because they have a common ancestor such as a grandparent from whom they inherited their genes through their parents. The closer the biological relationship is between relatives, the more likely that they will have the same faulty gene in common. A healthy child is the wealth of the nation and for the procreation of a healthy child apart from mentally and physically healthy parent, it is important that the couple should be mutually of a different clan. Among genetic disorders, Autosomal recessive disorders are strongly associated with consanguinity, approximately 30% of sporadic undiagnosed cases of mental retardation, congenital anomalies and dysmorphism may have an Autosomal recessive etiology with risks of recurrence in future pregnancies.